Does Economic Growth Mediate Investment, Inflation, and Human Development Investment on Poverty in Indonesia? - Agam Fitriady; Vivi Silvia; Suriani Suriani (Faculty of Economic and Business Syarif Hidayatullah State Islamic University of Jakarta, 2022)
Poverty is a classic yet interesting topic of discussion because the problem of poverty has not been solved. This study analyzed the role of economic growth in mediating the effects of investment, inflation, and Human Development Investment (HDI) on poverty in Indonesia. Using the multiple regression method of path analysis and the data from 32 provinces in Indonesia, the results showed that investment had a positive effect on economic growth and poverty, but inflation had no effect on economic growth and poverty while HDI had a positive effect on economic growth but a negative effect on poverty. Economic growth mediated the effect of investment and HDI, but not the effect of inflation on poverty. Hence, it can be said that it is not enough for the government to only prioritize economic growth, optimal investment, a higher level of HDI, and a stable inflation rate. They must also strive to reduce inequality between regions, support labour-intensive, well-targeted and direct investments in the real sector, and involve all stakeholders to achieve an effective and efficient national development in the context of poverty reduction.How to Cite:Fitriady, A., Silvia, V., & Suriani. (2022). Does Economic Growth Mediate Investment, Inflation, and Human Development Investment on Poverty in Indonesia? Signifikan: Jurnal Ilmu Ekonomi, 11(2), 437-456. https://doi.org/10.15408/sjie.v11i2.26145.JEL Classification: C33, E22, O11